Teaching children English as an additional language [ a programme for 7-11 year olds - Scott, Caroline , 1976- (Routledge, 2009)
Out of the thirty children, two-thirds speak a different language at home and only speak English at school. This book solves this problem with a ten-week teaching programme of units and lesson activities for children aged seven-eleven (Key Stage 2) new to English. It helps EAL teachers to identify learners' individual needs